Economic Evaluation of Landscape Integrated Pest Management Programs in Banyumas Regency, Central Java, Indonesia - Perwitasari, Hani; ., Irham; Hartono, Slamet; Hardyastuti, Suhatmini (International Journal of Engineering and Technology, 2018)
The massive use of chemicals in food production process has adversely affected the aspect of cost, ecology and health in particular. Landscape Integrated Pest Management (LIPM) Program is one of the technology applications targeted to minimize the chemicals. In Indonesia, there were only 6 regencies which applied LIPM, which included Banyumas regency. This study primarily aims at comparing production costs, productivity, revenue, profit and financial feasibility between LIPM and non-LIPM rice farms. The researchers collected primary and secondary data during the investigation. They purposively chose Pliken Village as the research object as it is the only village implementing LIPM. Meanwhile, sample was selected by random sampling methods involving LIPM and non- LIPM farmers with 30 respondents for each. Independent-samples T test was exerted to compare productivity, revenue, cost, profit and financial feasibility. The results indicate that productivity, revenue, profit and financial feasibility farming with LIPM were higher than the non-LIPM farming. Moreover, the production cost in the LIPM farming was lower than the production cost of the non-LIPM farming. The independent T-test pinpoints that the total revenue indicator and profit were significant. In other words, it may become reference to encourage farmers to apply Landscape Integrated Pest Management Program for sustainable agricultureÂ